Pardon Power of the President of North Macedonia – Uses and Misuses - Renata Treneska Deskoska (Perspectives of Law and Public Administration, 2023)
The President of the Republic of Macedonia, Gjorge Ivanov in 2016 pardoned 56 individuals. Some of them were pardoned more than once (the former Minister for Transport and Communications was pardoned 16 times, the former Minister for Interior was pardoned 13 times etc.). Most of the pardoned persons were politicians or their close collaborators. The President’s explanations for the pardons were that he sought to help the country overcome political crisis, that the country had been facing for almost two years. This event raised many questions about the constitutional aspects of the pardons in North Macedonia, which will be analyzed in this paper. The analysis show that these pardons were unlawful and the presidential power was misused. Because similar questions about misuse of presidential pardons were debated in USA under Trump rule, this paper will also make comparisons of the (mis)use of presidential power to grant pardons in North Macedonia and in the USA. At the end the paper will discuss the possible legal solutions for overcoming the misuse of this power of the President of North Macedonia.
Keywords: pardons, Constitutional Court, President of the Republic, North Macedonia.